2019 International Conference on Robotics and Automation (ICRA) 2019
DOI: 10.1109/icra.2019.8793261
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Granularity Human-Swarm Interaction

Abstract: We present an augmented reality human-swarm interface that combines two modalities of interaction: environment-oriented and robot-oriented. The environmentoriented modality allows the user to modify the environment (either virtual or physical) to indicate a goal to attain for the robot swarm. The robot-oriented modality makes it possible to select individual robots to reassign them to other tasks to increase performance or remedy failures. Previous research has concluded that environment-oriented interaction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…Through enabling a human-friendly visualization of how a robot is perceiving its environment, an improved human-in-the-loop model can be achieved ( Sidaoui et al, 2019 ; Gong et al, 2017 ). The use of AR technology for robotics has been elevated by the aid of several tools, mainly Vuforia Engine ( Patel et al, 2019 ; Makita et al, 2021 ; Comes et al, 2021 ), RosSharp ( Kästner and Lambrecht, 2019 ; Rosen et al, 2019 ; Qiu et al, 2021 ), ARCore ( Zhang et al, 2019 ; Chacko et al, 2020 ; Mallik and Kapila, 2020 ), and ARKit ( Feigl et al, 2020 ; McHenry et al, 2021 ). ARCore and ARKit are tools that have enhanced the AR experience for motion tracking, environmental understanding, light estimation, among other features.…”
Section: Discussionmentioning
confidence: 99%
“…Through enabling a human-friendly visualization of how a robot is perceiving its environment, an improved human-in-the-loop model can be achieved ( Sidaoui et al, 2019 ; Gong et al, 2017 ). The use of AR technology for robotics has been elevated by the aid of several tools, mainly Vuforia Engine ( Patel et al, 2019 ; Makita et al, 2021 ; Comes et al, 2021 ), RosSharp ( Kästner and Lambrecht, 2019 ; Rosen et al, 2019 ; Qiu et al, 2021 ), ARCore ( Zhang et al, 2019 ; Chacko et al, 2020 ; Mallik and Kapila, 2020 ), and ARKit ( Feigl et al, 2020 ; McHenry et al, 2021 ). ARCore and ARKit are tools that have enhanced the AR experience for motion tracking, environmental understanding, light estimation, among other features.…”
Section: Discussionmentioning
confidence: 99%
“…The pilots in the study reported that the monitoring of the swarm was complex and that more swarm autonomy and control options are required. Patel et al [10] use an interface with augmented reality to specify the overall goal for the swarm with a mixture of robot and environment-oriented modalities. We use a more informative visualization compared to [9] and there is flexible autonomy that allows the operator to adjust the autonomy of the swarm by modifying the messages that are exchanged with the UAVs [11].…”
Section: Introductionmentioning
confidence: 99%
“…We use a more informative visualization compared to [9] and there is flexible autonomy that allows the operator to adjust the autonomy of the swarm by modifying the messages that are exchanged with the UAVs [11]. The operator can choose to not intervene and grant full autonomy to the swarm, which makes our study different from [10]. There are also other studies that focus on the autonomy level of the swarm [12,13], different human-swarm interaction methods [10,14,15] and visualization techniques for the human-swarm systems [8,16] but this paper advances the state of the art in the following ways:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experimental evaluation is based on a study that involved 18 operators, grouped in teams of 2, and 9 real mobile robots involved in an object transport scenario. This paper takes advantage of our previous work on multi-granularity [17] interface design, in which we showed which interaction modalities [18] and which graphical elements of a user interface [19] provide the best performance in a multi-operator setting.…”
Section: Introductionmentioning
confidence: 99%